Time to laugh funny tales from here and there - Fenner, Phyllis Reid 1899-; Pitz, Henry Clarence 1895-1976. (New York Knopf, 1942)
Twenty humorous stories, told or retold by Hans Christian Andersen, Lucretia P. Hale, Ruth Sawyer, Parker Fillmore, Seumas MacManus, and Howard Pyle.
Keywords: Children's stories; Humorous stories; Short stories